Nursing law, jurisprudence and professional ethics - De Belen, Rustico T.; De Belen, Donna Vivian V. (Quezon City : C&E Pubishing, Inc., 2007)
This book is amodest attempt of the authors to make nursing students more ethico-legal conscious and steadfast in the pursuit of their noble goal-nursing.
Part I. Introduction to nursing law, jurisprudence, and professional ethics -- Chapter I : Nursing law, jusrisprudence and ethics : an overview -- Part II. Legal bases of nursing education, nursing regualtion, and nursing practice -- Chapter II : Nursing education -- Chapter III : Nursing regulation -- Chapter IV : Nursing practice -- Part III. Law and jurisprudence in the nursing profession -- Chapter V : Nursing law and jurisprudence -- Chapter VI : Jurisprudence in nursing practice -- Part IV : Professional ethics and standards in nursing -- Chapter VII : Principles in nursing ethics -- Chapter VIII : Ethics and standards in nursing
Includes bibliographical references and index.
Keywords: NURSING -- LAW AND LEGISLATION; NURSING ETHICS